Association Between Maternal Anemia and the Incidence of Postpartum Hemorrhage: A Study at Dr. H. Koesnadi General Hospital, Bondowoso - Wiwit Indriyani Aslina; Silviatul Amalia (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Postpartum hemorrhage (PPH) constitutes a critical obstetric emergency arising subsequent to either vaginal birth or cesarean delivery. Its defining characteristic is a quantifiable blood loss surpassing a volume of 500 milliliters. PPH underscores its significance as a major factor influencing both the prevalence of maternal illness and the rates of maternal death in Indonesia and globally. This study aimed to examine the effect of anemia in pregnant women on the PPH incidence at dr. H. Koesnadi General Hospital, Bondowoso, in 2018. The design used a retrospective study with a cross-sectional. The population consisted of 57 postpartum mothers, with 46 respondents as samples determined using Slovin's formula. Probability sampling technique was employed, specifically simple random sampling. Data acquisition was conducted utilizing a standardized checklist, and subsequent statistical analysis involved the application of the Chi-Square test, executed via SPSS version 25. The analysis yielded a statistically significant result, with a p-value of 0.001 (p<0.05), leading to the rejection of the null hypothesis. Consequently, the findings indicate a significant association between the presence of anemia and the PPH occurrence. In anemic pregnant women, reduced oxygen supply leads to fatigue and inadequate uterine muscle contractions, resulting in postpartum hemorrhage.